Life history of the land snail Habroconus semenlini (Stylommatophora: Euconulidae) under laboratory conditions - Silva, Lidiane (2009)
Habroconus semenlini is a micro-terrestrial gastropod native to South America. There are no previous studies on its biology. We studied its pattern of growth, fertility and lifespan under laboratory conditions. For this purpose, 80 snails were either grouped or kept isolated (40 animals in each condition) during their lifetime. Growth is indeterminate and the species is capable of self-fertilization with high reproductive success. Grouped snails had lower fecundity than the animals that were kept in isolation. This species has a short lifespan and only one reproductive period, which characterizes the occurrence of semelparity.